Illocutionary Speech Acts in the Novel Irtitām Lam Yusma‘ Lahu Dawiyy by Bothayna Al-Essa: A Pragmatic Analysis Study - Binta Thaila Khotrunnada; Buana, Cahya; Raharja, Hatta; Thamrin, Muhammad Husni (Universitas Muhammadiyah Yogyakarta, 2026)
This study analyzes illocutionary speech acts in the novel “Irtitām Lam Yusma‘ Lahu Dawiyy” (A Crash That He Did Not Hear) by Bothayna Al-Essa, using John Searle's speech act theory as the analytical framework. The research employs a descriptive qualitative approach with library research as the method. Data were collected through an in-depth reading of the novel, the identification of utterances containing illocutionary speech acts, and classification according to Searle's theory. The findings show that three examples of utterances were found for each type of illocutionary speech act: assertives, directives, expressives, and commissives, along with one utterance classified as a declarative illocutionary speech act. This study concludes that language in the novel not only functions as a means of communication but also serves as a tool for building emotional relationships and representing sociocultural tensions. Theoretically, this research contributes to the study of Arabic literary pragmatics, while practically, it can be utilized in the teaching of Arabic language and literature at the university level.